2013
DOI: 10.7585/kjps.2013.17.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Control Effects of Frankliniella occidentalis by using Trap Plants and Orius laevigatus in Chrysanthemum PVC House

Abstract: F. occidentalis (WFT, western flower thrips) is a major pest in artificial chrysanthemum houses. Nnumber of WFT attracted to yellow sticky trap was highest at trap plant and lowest at 15 and 20m places away from trap plant. Number of WFT attracted to yellow stick trap when trap plant was placed in chrysanthemum house 30 days after planting (resident WFT) was 4.4~7.7 times more than at 5 and 10 m places away from trap plant and when trap plant was placed in chrysanthemum house immediately after planting (reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Another research indicated that trap plants are more effective when placed in the chrysanthemum house immediately after planting (resident WFT). Also it was demonstrated that a combination of trap plants and chemical control is useful in the control of F. occidentalis (Choi et al 2013). A novel method, push-pull strategy, involves the behavioural manipulation of insect pests and their natural enemies by the combination of stimuli that acts to make the crops unattractive or unsuitable to the pests (push) while luring them toward an attractive source (pull).…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%
“…Another research indicated that trap plants are more effective when placed in the chrysanthemum house immediately after planting (resident WFT). Also it was demonstrated that a combination of trap plants and chemical control is useful in the control of F. occidentalis (Choi et al 2013). A novel method, push-pull strategy, involves the behavioural manipulation of insect pests and their natural enemies by the combination of stimuli that acts to make the crops unattractive or unsuitable to the pests (push) while luring them toward an attractive source (pull).…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%